Prevalence and severity of DSM‐5 eating disorders in a community cohort of adolescents. Issue 6 (5th June 2014) - Smink, Frédérique R.E.; van Hoeken, Daphne; Oldehinkel, Albertine J.; Hoek, Hans W.
ABSTRACT Objective The fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM‐5) includes a considerably revised eating disorder section. The aim of this study was to establish the prevalence and severity of eating disorders based on the new DSM‐5 criteria in a community cohort of adolescents. Method This study is part of TRAILS (TRacking Adolescents' Individual Lives Survey), a Dutch cohort study on mental health and social development from preadolescence into young adulthood. At baseline, the participants (n = 2, 230) were about 11 years old. Body mass index was measured at all four assessment waves. At age 19, the Composite International Diagnostic Interview was administered to 1, 584 of the participants. A two‐stage screening approach was used to estimate the prevalence of DSM‐5 eating disorders. Adolescents at high risk for eating disorders (n = 312) were selected for an additional interview administered by eating disorder experts. Results Of the high‐risk group n = 296 (95%) could be interviewed. Among the women, the lifetime prevalence of DSM‐5 anorexia nervosa was 1.7%, of bulimia nervosa 0.8% and of binge eating disorder 2.3%. Eating disorders were relatively rare among the men. The severity of most cases was mild to moderate and detection and treatment rates depended on the level of severity. Discussion The most common DSM‐5 eating disorder diagnoses in adolescents in the community are anorexia nervosa and binge eating disorder. Severity ratings for eating disorders seem valid in terms of both the distribution in the community and the correlation with detection and treatment by health care services. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2014; 47:610–619)